2000
DOI: 10.1016/s0306-4573(99)00056-4
|View full text |Cite
|
Sign up to set email alerts
|

Real life, real users, and real needs: a study and analysis of user queries on the web

Abstract: major Internet search service. We provide data on: (i) sessions -changes in queries during a session, number of pages viewed, and use of relevance feedback, (ii) queries -the number of search terms, and the use of logic and modifiers, and (iii) terms -their rank/frequency distribution and the most highly used search terms. We then shift the focus of analysis from the query to the user to gain insight to the characteristics of the Web user. With these characteristics as a basis, we then conducted a failure anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
657
6
16

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,064 publications
(731 citation statements)
references
References 12 publications
31
657
6
16
Order By: Relevance
“…Real-life searchers often prefer very short queries [1,4]. They may also avoid excessive browsing [1,9].…”
Section: User Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Real-life searchers often prefer very short queries [1,4]. They may also avoid excessive browsing [1,9].…”
Section: User Behaviormentioning
confidence: 99%
“…Recent studies show that real users of information retrieval (IR) systems search by very short queries but may try out several queries in a session [1][2][3][4][5]. Such queries may consist of only 1-2 search keys.…”
Section: Introductionmentioning
confidence: 99%
“…• Advanced search features such as Boolean operators are not used much, and users often make mistakes in using them [375].…”
Section: Transactional Queriesmentioning
confidence: 99%
“…This presents quite a challenge, especially when search engine queries are rather short. Studies by Spink et al [16] [27] have shown that the average query length is between two and three keywords. Moreover, these requests tend to cover a rather wide variety of information needs, and are often expressed with ambiguous terms.…”
Section: Introductionmentioning
confidence: 99%